Mechanical and thermal properties of surface treated sugar palm fibre-reinforced epoxy biocomposites - Mohamed Latiff, Ahmad Syahmi (2019)
A number of chemical treatment processes of natural fibres such as jute, kenaf, sisal, flax etc have been practised to improve the structure of natural fibre in order to help them to form a strong bonding with resin in bio-composites making. However, as for sugar palm fibre there are not many treatments available due to limited research has been done on it. The only treatments that can be found for sugar palm fibre are sodium hydroxide (NaOH) and sea water treatments. This thesis focused on the study of new treatment for sugar palm fibre which is benzoylation (benzoyl chloride) treatment. The purpose of benzoylation is to reduce the hydrophilicity of sugar palm fibre and improve its chemical interlocking at the interface. This helps the fibre to be more compatible with polymer matrix and form a strong bonding. The mechanical properties of both untreated and treated sugar palm fibres were studied. The sugar palm fibres were being treated with sodium hydroxide and benzoyl chloride respectively to alter the composition of the fibre and to improve its properties. In single fibre testing, the highest improvement in tensile strength was observed in fibre treated with benzoyl chloride for 30 minutes soaking time with increment of 47.5 % compared to untreated fibre. The second highest was fibre treated with NaOH, showing increment of 35.1 % compared to untreated fibre. For sugar palm composite with 30 % fibre loading, the fibre treated with NaOH showed highest tensile strength with value of 54.8 MPa, followed by fibre treated with benzoyl chloride with 54 MPa and lastly untreated fibre with 38.3 MPa. For thermal properties, benzoylation process show significant improvement in all testing performed which are thermogravimetric analysis (TGA), dynamic mechanical analysis (DMA), thermomechanical analysis (TMA) and differential scanning calorimetry (DSC). This show that benzoylation process gives the fibre and its composites a better thermal stability than other composites. Based on the results obtained, it can be concluded that both benzoyl chloride and sodium hydroxide treatments improved the properties of sugar palm fibres and its composites.